2019
DOI: 10.1136/bmjopen-2018-028364
|View full text |Cite
|
Sign up to set email alerts
|

Prospective longitudinal observational study of the macro and micro haemodynamic responses to septic shock in the renal and systemic circulations: a protocol for the MICROSHOCK – RENAL study

Abstract: IntroductionSeptic acute kidney injury (AKI) is the most common complication of septic shock and increases mortality. A large body of experimental data suggests alterations in renal perfusion occur, but this is yet to be fully assessed in humans. The aim of the current study is to observe the macro and microcirculations in both the systemic and renal circulations in a cohort of patients with early septic shock.Methods and analysisSingle-centre, prospective, longitudinal, observational study of 50 patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…A reduction in variables reflective of blood volume and blood flow was observed in both groups, but with greater variability in patients with sepsis associated AKI. This heterogeneity may be a result of sub-phenotypes of septic AKI, where a variety of changes occur in response to a septic insult and is the subject of ongoing study (11,24). Additionally, the greater urine output observed in the septic group raises the possibility that some of these patients may have been recovering renal function at the time CEUS measurements were performed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A reduction in variables reflective of blood volume and blood flow was observed in both groups, but with greater variability in patients with sepsis associated AKI. This heterogeneity may be a result of sub-phenotypes of septic AKI, where a variety of changes occur in response to a septic insult and is the subject of ongoing study (11,24). Additionally, the greater urine output observed in the septic group raises the possibility that some of these patients may have been recovering renal function at the time CEUS measurements were performed.…”
Section: Discussionmentioning
confidence: 99%
“…Our group is currently recruiting to an ongoing study, Microshock Renal (Clinicaltrials.gov NCT03713307) which aims to explore the pathogenesis of septic AKI and in particular the contribution of hypoperfusion in patients with septic shock. The protocol for this study has been published elsewhere and uses a relatively new technique, contrast-enhanced ultrasound (CEUS), to visualize perfusion within the renal parenchyma, alongside measures of global renal blood flow and cardiac output (11).…”
Section: Introductionmentioning
confidence: 99%
“…Serial assessments were made of the renal and systemic macro-and microcirculatory state using CEUS, transthoracic echocardiography and sublingual video microscopy at 4 time points: Day zero (D0) within 24 h of ICU admission, D0 + 24 h (D1), D0 + 48 h (D2) and D0 + 96 h (D4). The study protocol was published prior to data analysis [11].…”
Section: Methodsmentioning
confidence: 99%
“…Most studies have found the involvement of three factors in its pathophysiological process: Inflammation, 4,5 diffuse microcirculation blood flow abnormality, 6 and bioenergy‐adaptive response of cells to injury 7,8 . The changes in renal blood perfusion, including macroscopic (larger blood vessels such as renal artery) and microscopic circulation (smaller vessels typically less than 20 μm in diameter, where cellular substrate delivery occurs), 9 seem to play a vital role in the occurrence of acute renal injury 10 . Prowle et al found that renal blood flow (RBF) decreased in septic kidney injury while studying great vessel blood flow 11 .…”
Section: Introductionmentioning
confidence: 99%